Outcomes of a GnRH Agonist Trigger Following a GnRH Antagonist or Flexible Progestin-Primed Ovarian Stimulation Cycle - Erkan Kalafat; Erkan Kalafat; Engin Turkgeldi; Sule Yıldız; Merve Dizdar; Ipek Keles; Baris Ata; Baris Ata (Frontiers in Endocrinology, 2022)
A suggested explanation for the pituitary-suppressive effects of progestin-primed ovarian stimulation cycles (PPOS) is pituitary luteinizing hormone (LH) depletion with progestin exposure during the follicular phase. The GnRH agonist (GnRHa) trigger releases endogenous LH from the pituitary, and if the LH depletion theory is correct, the response to the agonist trigger would be dampened in PPOS cycles. In this study, we compared the performance of the GnRHa trigger after PPOS and GnRH antagonist ovarian stimulation cycles. All women who underwent ovarian stimulation with the GnRH antagonist or flexible PPOS (fPPOS) and received a GnRH agonist trigger were eligible for inclusion. Outcomes included number of metaphase-II (MII) oocytes retrieved per cycle, rates of empty follicle syndrome, maturation, fertilization, blastulation, and cumulative clinical pregnancy per stimulation cycle. During the screening period, there were 166 antagonists and 58 fPPOS cycles triggered with a GnRH agonist. Groups were matched for potential confounders using propensity score matching. Progestin-downregulated cycles had 19% high mature oocyte yield (median: 14 vs. 19 MII oocytes, P = 0.03). Cumulative ongoing pregnancy or live birth rates were estimated after matching for transferred embryo count, and rates were similar between GnRH antagonist and fPPOS group (57.0% vs. 62.1%, P = 0.68). However, the number of remaining blastocysts was higher in the fPPOS group (median: 5.0 vs. 6.0, P < 0.001). LH levels were higher in fPPOS cycles compared to GnRH antagonist cycles up to the trigger day (P < 0.001). After the GnRHa trigger, fPPOS cycles were associated with a steeper LH surge compared with antagonist cycles (P = 0.02). Higher endogenous gonadotropin levels through the stimulation period and an LH surge of higher magnitude following a GnRHa trigger suggest a milder pituitary suppression by fPPOS, which needs to be confirmed in larger samples. It appears that progestins do not deplete pituitary LH reserves and a GnRHa trigger is usable after PPOS in women with high ovarian reserve.